2016
DOI: 10.1038/nature19090
|View full text |Cite
|
Sign up to set email alerts
|

Switching on electrocatalytic activity in solid oxide cells

Abstract: Solid oxide cells (SOCs) can operate with high efficiency in two ways-as fuel cells, oxidizing a fuel to produce electricity, and as electrolysis cells, electrolysing water to produce hydrogen and oxygen gases. Ideally, SOCs should perform well, be durable and be inexpensive, but there are often competitive tensions, meaning that, for example, performance is achieved at the expense of durability. SOCs consist of porous electrodes-the fuel and air electrodes-separated by a dense electrolyte. In terms of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
433
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(441 citation statements)
references
References 14 publications
8
433
0
Order By: Relevance
“…The growth of metal nanoparticles drastically improves the current density to 1.2 A cm −2 at 1.5 V when optimum alloy compositions are obtained. These values are comparable to the performances of nickel-decorated (La,Sr)(Ti,Mn)O 3+δ cathodes and La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3+δ prepared with an electrochemical switching method ( 14 , 23 ). The in situ impedance spectra in fig.…”
Section: Resultssupporting
confidence: 73%
“…The growth of metal nanoparticles drastically improves the current density to 1.2 A cm −2 at 1.5 V when optimum alloy compositions are obtained. These values are comparable to the performances of nickel-decorated (La,Sr)(Ti,Mn)O 3+δ cathodes and La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3+δ prepared with an electrochemical switching method ( 14 , 23 ). The in situ impedance spectra in fig.…”
Section: Resultssupporting
confidence: 73%
“…The Ti 2p spectra were deconvoluted and resolved into four spin orbit components at 2p3/2 binding energies 457.6, 458.14 eV and their corresponding 2p1/2 components (463.21, 464.0 eV) which are assigned as Ti 3+ (TiOOH/coordinatively unsaturated) and Ti 4+ (TiO 2 ), respectively [42,43]. The large ratio of Ti 3+ is suggested owing to the increased electron content of the lattice surface of TiO 2 within the voltage-driven reduction process [44]. The peaks at 284.24, 285.44 and 287.99 eV for C 1 s spectrum are ascribed to the C–C bond with sp 2 orbital, C–O and C=O bonds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a broad sense, exsolution refers to the process of releasing compositional elements from the perovskite lattice to form nanoparticles anchored on the surface, with the driving force being the oxygen partial pressure gradient between the oxide lattice and external environment. This process can occur through “electrochemical switching” (a term recently initiated by Irvine and co‐workers) or through reduction by hydrogen . For example, Zhou et al reported an intercalation/de‐intercalation mechanism of A‐site silver‐doped (La 0.8 Sr 0.2 ) 0.95 Ag 0.05 MnO 3− δ perovskite under polarization conditions ( Figure a), where Ag can be stripped from the lattice under cathodic polarization, forming Ag nanoparticle–modified A‐site‐deficient (La 0.8 Sr 0.2 ) 0.95 MnO 3− δ , and then restored into the perovskite lattice under anodic polarization.…”
Section: Synthetic Methods Of Nanostructured Perovskitesmentioning
confidence: 99%
“…For example, Zhou et al reported an intercalation/de‐intercalation mechanism of A‐site silver‐doped (La 0.8 Sr 0.2 ) 0.95 Ag 0.05 MnO 3− δ perovskite under polarization conditions ( Figure a), where Ag can be stripped from the lattice under cathodic polarization, forming Ag nanoparticle–modified A‐site‐deficient (La 0.8 Sr 0.2 ) 0.95 MnO 3− δ , and then restored into the perovskite lattice under anodic polarization. More recently, Irvine and co‐workers observed the exsolution of Ni nanoparticles on the surface of La 0.43 Ca 0.37 Ni 0.06 Ti 0.94 O 3− γ perovskite upon the application of a 2 V potential at 900 °C . Compared with conventional reduction by hydrogen, such electrochemical switching happens faster (almost instantly), causes a higher extent of exsolution, and produces a greater particle population at a smaller average particle size.…”
Section: Synthetic Methods Of Nanostructured Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation